Senescent cells as new pharmacological targets for age-related diseases and anti-aging therapy - Masternak, Michal M. (Journal of Medical Science, 2023)
Aging is a natural process leading to decline in physical function, reducing ability to adjust to everyday organismal stress and increased frailty. Recent studies of the mechanism of aging have brought attention to naturally occurring senescent cells in different organs throughout the body. This natural process of senescence is caused by cell cycle arrest due to cellular damage, which protects cells from apoptosis, while stimulating the production and secretion of different senescent associated secretory phenotypes (SASPs) causing low grade chronic inflammation. Emerging studies show that by targeting and eliminating these cells with a new class of senolytic drugs in old animals we can improve a variety of health conditions including reduction of inflammation, improvement of insulin sensitivity and metabolic status, increase of bone mineral density and enhanced physical function together with extended overall longevity. Ongoing clinical trials using Desatanib and Quarcetin (D+Q) and other classes of senolytic drugs indicate high translational potentials in targeting and clearing senescent cells to cure some age-related diseases; however, more in depth studies have to be completed to incorporate these therapies in general healthy elderly populations for safe anti-aging intervention.
Keywords: aging; senescence; senolytics